2015
DOI: 10.1007/s13224-015-0773-y
|View full text |Cite
|
Sign up to set email alerts
|

Clinicopathological Study of Uterine Leiomyomas: A Multicentric Study in Rural Population

Abstract: Background and Objectives Leiomyoma of uterus forms the most common type of benign tumor of uterus and also the most common pelvic tumor in women. The symptomatology continues to be variable. Surgery has for long been the main mode of therapy for the myomas. For women who wish to retain the uterus for future pregnancies or other reasons, myomectomy is preferred. Recent trend has been toward nonsurgical approaches like GnRH hormone analogs/agonists, RU 486, or selective uterine artery embolization, laparoscopic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
8
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(11 citation statements)
references
References 11 publications
3
8
0
Order By: Relevance
“…In our study subserosal fibroids were 24.34% and submucosal fibroids were 4.27%. Extrauterine occurrence of cervical fibroids was seen in 0.82% cases while it was 2-8% in similar studies by Dayal et al, 14 Kulkarni et al 15 and Geethamala et al 12 Two cases in our study had broad ligament fibroids which can sometimes be confused with ovarian mass.…”
Section: Variantsupporting
confidence: 71%
See 1 more Smart Citation
“…In our study subserosal fibroids were 24.34% and submucosal fibroids were 4.27%. Extrauterine occurrence of cervical fibroids was seen in 0.82% cases while it was 2-8% in similar studies by Dayal et al, 14 Kulkarni et al 15 and Geethamala et al 12 Two cases in our study had broad ligament fibroids which can sometimes be confused with ovarian mass.…”
Section: Variantsupporting
confidence: 71%
“…Dual pathology of adenomyosis and leiomyomas were noted in 31.07% of patients in present study similar to studies by Geethamala et al (29.1%), 12 Gowri et al (29%) 18 and Kaur et al (27.69%). 13 However studies by Lahori et al (19.23%) 11 and Kulkarni et al (16%) 15 show lower incidence. Coexistence of these lesions may be due to unopposed estrogenic stimulation.…”
Section: Variantmentioning
confidence: 90%
“…They are seldom found earlier than puberty and quit to develop after menopause. 17 Begum S et al described that multiparous women were found to own fibroids greater often than nulliparous in their perimenopausal years which indicates their characteristics slow development rate. 18 The findings of our study also showed that fibroids are more common in multiparous women as compared to nulliparous/ primiparous.…”
Section: Discussionmentioning
confidence: 99%
“…Cervical leiomyomas are quite uncommon. 8 The pathophysiology of leiomyomas suggests that they develop as a result of the proliferation of smooth muscle cells and connective tissue. Smooth muscle cells are shown to proliferate monoclonally.…”
Section: Discussionmentioning
confidence: 99%